Family satisfaction with intensive care services: A survey from three tertiary hospital units - Ali, Ayman; Krishnareddy, Kalpana; Loney, Tom; Hon, Hubert (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Objectives: We aimed to investigate the level of family satisfaction in three intensive care units (ICUs) in a tertiary hospital in the United Arab Emirates, which is a multicultural society. Methods: This was a cross-sectional study. Family members of patients who were admitted to the ICU for more than 48 h were included in the study. Families were approached with a validated FS24-ICU Family Satisfaction Survey Questionnaire. One hundred questionnaires were collected over 3 months from January 1, 2016, to March 31, 2016, in the pediatric medical-surgical and cardiac, adult cardiac, and adult medical/surgical ICUs. Results: The overall level of satisfaction measured as total satisfaction score, medical care score, and decision-making score were 75.1 ± 14.2, 80.1 ± 18.6, and 68.1 ± 11.5, respectively. These results are comparable to other high-income and developed countries. Conclusions: This is the very first study from the UAE demonstrating a high level of patient family satisfaction in both adult and pediatric ICUs. This study also highlighted areas where further improvement needs to occur.
Keywords: Care; communication; environment; family satisfaction; intensive care units; United Arab Emirates